Generation of precipitations and flow rates from maximum avenues for the basin of the Biabo river - Carmona , Abel (2021)
This work focuses on the calculation and validation of the parameters used for the generation of flows of maximum avenues along 16 points of interest in the main channel of the Biabo river. Due to insufficient information from meteorological and hydrometric measurements within the basin, the daily precipitation grid information from the PISCO database v2.1 of SENAMHI was used, the model of frequency duration curves from the ILLA-SENAMHI-UNI study, and the Snyder unit hydrograph, and the results obtained were calibrated based on the records of maximum flows from the Requena-Biabo hydrometric station. Thus, for example, for the Requena-Biabo station basin, the comparison between the flows of maximum floods generated with the flows recorded in for different return times, the error obtained fluctuates between ± 5%.